Methanolic extracts ofthreeweeds as botanical fungicides to controlpeanut rust disease - ERIYANTO YUSNAWAN; ALFI INAYATI (Smujo International, 2016)
Abstract. Yusnawan E, Inayati A. 2016. Methanolic extracts of three weeds as botanical fungicides to control peanut rust disease. Nusantara Bioscience 8: 117-122. Rust disease caused by Puccinia arachidis is one of the most important diseases on peanuts. Ageratum (Ageratum conyzoides L.), spiny amaranth (Amaranthus spinosus L.), and coco-grass (Cyperus rotundus L.) had the ability to inhibit plant pathogens. The aim of the research was to obtain the weed extracts effective to control peanut rust disease. The three weeds were ground to obtain fine particles, macerated in methanol for 18 h and evaporated the solvent using vacuum rotary evaporator. Methanolic crude extracts obtained from ageratum, coco-grass, and spiny amaranth at concentrations of 0.1%, 1.0%, 2.5%, and 5.0% were applied to the uredospores and peanut plants infected with the pathogen. Applications of 5% ageratum and 5% coco-grass extracts suppressed the spore germinations by 78 to 80% and 76 to 80%, respectively. Disease intensities on Kancil cultivar treated with 5% crude extract of ageratum were 18 to 22% and 29 to 31% after three and four times of extract applications. Disease intensities on untreated plants were 30 to 32% and 43 to 46%, whereas the chemical application suppressed the disease intensities up to 16 to 18% and 15 to 17% at the same time of observation. Preliminary phytochemical screenings showed that the methanolic extract of ageratum contained alkaloids, flavonoids, tannins, saponins, and terpenoids. Crude extract of 5% ageratum was effective to control rust disease on peanuts, therefore, could be used as an alternative control agent to suppress the disease.